Discussing The Use of Public Goods for Private Ends - Trubina, Elena (Javnost-The Public, 2020)
How to make sense of the face-to-face public discussion of the distribution of public funds? In this article, I argue that physical co-presence of citizens in course of collective deliberation gives the underrepresented social groups opportunities to speak out their concerns and express their social positions. In a discussion that I co-organised with support of a few local cultural organisations, participants faced a possibility to practice critical debates regarding the decisions of the municipal, regional and central authorities. I present a case study that contributes to the literature by describing the “openings” in public indifference that have implications for practice and policies. I reflect on the public discussion as an opportunity to engage into a dialogue a general public, activists, scholars, officials and experts and imagine alternative ways for democratic deliberation. This article links together the problems of distribution of public goods and engaging public into the organisation of mega-events in the light of the predicaments of the capitalist urban development.